1985
DOI: 10.1073/pnas.82.8.2498
|View full text |Cite
|
Sign up to set email alerts
|

Combination of long-acting microcapsules of the D-tryptophan-6 analog of luteinizing hormone-releasing hormone with chemotherapy: investigation in the rat prostate cancer model.

Abstract: The effect of combining hormonal treatment consisting of long-acting microcapsules of the agonist [D-Trp6]LH-RH (the D-tryptophan-6 analog of luteinizing hormone-releasing hormone) with the chemotherapeutic agent cyclophosphamide was investigated in the Dunning R-3327H rat prostate cancer model. Microcapsules of LH-RH formulated from poly(DL-lactide-co-glycolide) and calculated to release a controlled dose of 25 pg/day were injected intramuscularly once a month. Cyclophosphamide (Cytoxan) (5 mg/kg of body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Survival days of rats castrated on days 200 and 250 were similar to average survivals of intact, untreated control rats inoculated with the same tumor (350 days). A similar effect resulting from androgen ablation was observed with an LH-RH agonist [3]. In the autochthonous transgenic adenocarcinoma mouse prostate (TRAMP) model, early castration or treatment with an antiandrogen, flutamide, also significantly reduced tumor growth and improved tumor-free survival [4][5][6].…”
Section: Supporting Experimental Datamentioning
confidence: 83%
“…Survival days of rats castrated on days 200 and 250 were similar to average survivals of intact, untreated control rats inoculated with the same tumor (350 days). A similar effect resulting from androgen ablation was observed with an LH-RH agonist [3]. In the autochthonous transgenic adenocarcinoma mouse prostate (TRAMP) model, early castration or treatment with an antiandrogen, flutamide, also significantly reduced tumor growth and improved tumor-free survival [4][5][6].…”
Section: Supporting Experimental Datamentioning
confidence: 83%
“…Tumors and various organs were removed, cleaned, carefully weighed, and then quickly frozen on dry ice. Serum levels of testosterone, prolactin, and LH were measured using radioimmunoassays as described previously [36,38,43]. All data are expressed as mean SE.…”
Section: Methodsmentioning
confidence: 99%
“…All data are expressed as mean SE. Statistical analyses were performed using a computer-assisted program as previously described [36,43].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isaacs [75], using serially transplantable androgen-sensitive Dunning R3327H rat prostate adenocarcinoma as a model, found that castration had no effect when performed 250 days after tumour inoculation, but did extend survival (350 -470 days) if implemented at the same time as tumour inoculation. In another study [76], the combination of hormonal therapy (a long-acting LHRH microcapsule) with chemotherapy (cyclophosphamide) enhanced the therapeutic response, possibly by inhibiting the proliferation of both androgendependent and androgen-independent cells. These preclinical observations led to clinical trials investigating the benefits of adjuvant hormonal therapy and chemotherapy.…”
Section: Adjuvant Hormonal Therapymentioning
confidence: 97%